Integrating Tools to Support Software Measurement - Fonseca, Vinícius Soares; Barcellos, Monalessa Perini; Falbo, Ricardo de Almeida (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2016)
Software measurement is a key practice to process improvement and project management. Given the nature of measurement activities, supporting tools are essential. Different tools can be combined to support the measurement process and provide necessary information for decision making. However, these tools are usually developed by different developers, at different points in time and without concern for integration. As a result, organizations have to deal with integration issues to allow tools communication and properly support the measurement process. In this paper we present a tool integration initiative performed following the Ontology-Based Approach for Measurement Systems Integration (OBA-MSI) aiming to support the measurement process in a software development organization. The integration involved three tools: Taiga, SonarQube and SoMeSPC.